주의력결핍,과잉행동장애의 한의학 치료동향 (2005-2006년 중국 임상 논문 중심으로) - 박현철; Hyun Chul Park; 강문수; Mun Su Kang; 김락형; Lak Hyung Kim (동의신경정신과학회지, 2007)
Objective : The purpose of this study is to take around the oriental medical treatment about Attention Deficit Hyperactivity Disorder in China.Method : We reviewed the 22 studies about ADHD which were published from 2005 to 2006. We selected those studies from CNKI (中國知識基礎設施工程 http://www.cnki.net). Result : We could find 22 studies about ADHD in CNKI from 2005 to 2006. DSM (III-R of IV) was used frequently in the diagnosis of ADHD. Herbal medicines, acupuncture, auricular therapy, moxibustion, chuna treatment, cupping therapy were used in the treatments of ADHD. Differentiation of syndromes-Eum deficiency, heart and spleen deficiency, Damwha- was important in the diagnosis and treatments of ADHD in TCM. Jang and Bu(the internal organs; 臟腑) concerned in differentiation of syndromes about ADHD were Liver 肝, Kidney , Heart 心, Spleen 脾.Most of studies reported very good results compared with western medicine treatment-Ritalin medication. Conclusion :There have been reported many ADHD clinical studies in China and these studies can be applied to the clinical practices in Korea.